Cultural Capital and Educational Success: A Systematic Review of Bourdieu’s Theory in Contemporary Educational Sociology - Hikmat (Global Writing Academica Researching & Publishing, 2024)
This article presents a systematic review of Bourdieu’s theory of cultural capital in relation to contemporary educational success. The study aims to synthesize and critically evaluate the existing body of literature that applies Bourdieu’s framework to educational sociology. A literature review method was employed, focusing on peer-reviewed articles published in leading journals across sociology and education. The analysis highlights how cultural capital, manifested through language proficiency, cultural practices, and family background, continues to shape academic achievement. Findings reveal that the reproduction of social inequalities within schools remains strongly influenced by differences in cultural resources among students. Moreover, the review identifies variations in the interpretation of cultural capital across diverse socio-cultural contexts, particularly in non-Western educational systems. Several studies emphasize the adaptability of Bourdieu’s framework in explaining new forms of educational stratification in the era of globalization. At the same time, critical scholarship challenges the deterministic aspects of Bourdieu’s theory and calls for a more dynamic understanding of cultural practices. This review underscores the importance of integrating cultural capital with broader structural and policy considerations to foster equitable education. The article concludes that while Bourdieu’s theory remains highly relevant, it requires contextual reinterpretation to address contemporary educational challenges.